ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND DIGITAL MARKETING ON THE DECISION TO PURCHASE KRISTANABLE.ID HIJAB IN BANYUWANGI DISTRICT - Amalia, Risma; Nursaidah, Nursaidah; Rahayu, Jekti (Univesitas Muhammadiyah Tangerang, 2024)
This research aims to find out and analyze the influence of product quality, price and digital marketing on purchasing decisions at Kristanable.id in Banyuwangi. This type of research uses descriptive quantitative methods with a sample size of 95 respondents and uses data collection techniques in the form of questionnaires to respondents. The data analysis technique for this research uses instrument testing, classical assumptions and multiple linear regression. The analysis results obtained show that product quality, price and digital marketing have a positive and significant influence on purchasing decisions at Kristanable.id in Banyuwangi, with an influence contribution level of 0.574, which means 57.4%.